Antimicrobial Effects Of Three Different Herbal Intracanal Medicament Gels On Enterococcus Faecalis: A Comparative Invitro Study (Journal of Pharmaceutical Negative Results, 2023)
The antimicrobial efficacy of Triphala, Aloevera and Curcumin against Enterococcus faecalis have been established in previous studies, However, no comparative study with Chlorhexidine have been done so far. Methods and Material: Root canals of one hundred and forty-five extracted, straight single-rooted human teeth were contaminated with Enterococcus faecalis and initial bacterial count was determined after 4 weeks using CFU counts. Samples were then divided into five groups- Group 1- Saline, Group 2-Chlorhexidine, Group 3- Triphala, Group 4- Aloevera, Group 5- Curcumin. 1 ml of the prepared medicament was injected into the canals and after 7 days of incubation, the colony counts were performed. Dentin shaves were removed with Gates Glidden drills and a BHI broth saturated paper point and checked for turbidity using spectrophotometer. Results: The mean percentage reduction in bacterial count was greater in Group 2-Chlorhexidine (89.01%) followed by Group 3- Triphala group (70.99%), Group 5 – Curcumin (44.10%) and Group 4- Aloevera (38.44%). Conclusion: Chlorhexidine gluconate gel still remains as the gold standard against E. faecalis. Triphala and Curcumin also showed good antibacterial efficacy against E. faecalis.